IMBIBING CULTURAL ETHOS IN INTERIORS RESIDENTIAL SPACES IN AHMEDABAD - Jasani, Bhavi Minesh (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This research delves into the topic of incorporating cultural ethos into interior design, with a particular focus on residential spaces in Ahmedabad, Gujarat, India. Cultural elements play a significant role in interior design, alongside color, line and furniture. Ahmedabad is an excellent example of a city with a rich cultural heritage, where traditional and modern interior design styles can be distinguished from each other. The essay examines various design elements that showcase the cultural heritage of Ahmedabad, including traditional motifs, color palettes and locally sourced materials. The research explores the significance of socio-cultural values in Ahmedabad and how it affects the interior design of residential spaces. The aim of this research is to highlight the importance of cultural ethos in interior design and provide designers and architects with valuable insights for creating culturally rich and meaningful spaces. The findings indicate that incorporating cultural elements in residential interior design can create a unique and authentic living experience that celebrates the cultural heritage of the society. The study concludes that the integration of cultural ethos in interior design is essential to creating a harmonious and culturally rich living experience for residents.